Pengaruh Kemiskinan dan Prevalensi Stunting terhadap Indeks Pembangunan Manusia di Sumatera Barat - Oktaviani, Nichy; Handayani, Deby; Wati, Henny; Zaki (Jurnal Informatika Ekonomi Bisnis, 2024)
This research aims to determine the influence of poverty and the prevalence of stunting on the human development index in West Sumatra. This research is motivated by the large number of cases of poverty in West Sumatra, especially remote areas such as the Mentawai Islands Regency, which has resulted in the prevalence of stunting increasing and affecting the Human Development Index in West Sumatra. This research uses a quantitative type of research using secondary data. This research carries out classical assumption tests, hypothesis testing using SPSS. Looking at the results of the tests that have been carried out, it proves that poverty has no significant effect on the Human Development Index (HDI) with a significant value of 0.651 > 0.05, while the stunting prevalence variable has a significant effect on the Human Development Index (HDI) with a significant value of 0.003 < 0.05 , The results of poverty testing and stunting prevalence simultaneously have a significant effect on the Human Development Index (HDI) with a significant value of 0.001 < 0.05. This shows that poverty and stunting prevalence can predict information regarding the Human Development Index (HDI) 0.511 or 51.1%, while the remaining 0.489 or 48.9% is influenced by other factors not included in this research.